Gendered Distributive Injustice in Production Networks: Implications for the Regulation of Precarious Work. (3rd May 2022) - Marshall, Shelley; Taylor, Kate; Tödt, Sara
Abstract: This paper is concerned with how precarious work in gendered production networks can be regulated to address distributional injustices—examining the regulation of homework in Thailand as a case study. The contribution of this paper is to empirically analyse these outcomes of the organisation and governance of production as gendered distributional injustices. The analytic extends the distributive analysis employed by Shamir by applying feminist global production network scholarship developed by scholars such as Anne Tallontire, Catherine Dolan, Sally Smith, Wilma Dunaway and Stephanie Barrientos. Our aim is to capture the complex ways in which distributional injustices are created in gendered production networks by examining both distributional asymmetries between homeworkers and other actors along the value chain (vertical dynamics), as well as the way that local gender relations shape the social undervaluation of women's home-based work (horizontal dynamics). We draw on rich empirical research to describe these distributional asymmetries for homeworkers in the North-East of Thailand who repair faults in fishing net production for global markets. A handful of countries in the Economic South have reformed labour regulation to address capitalist innovation resulting in new models of production and accumulation. Thailand joined these ranks in 2010, but this has gone without notice in the comparative labour regulation literature. We interrogate the extent that the gendered distributional injustices we identify are corrected through the interventions of Thai labour regulation. We compare the Thai approach with International Labour Organisation Convention 177 (1996) Homework (referred to herein as the ILO Homework Convention or C177). We conclude by suggesting ways that the Thai approach could be strengthened, drawing in places on examples of labour regulation advances in other countries.